The Shariah Law in Pakistani Legal System and General Legal Status of Women in Pakistan - Hassan, Amna (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
This paper puts emphasizes on the prevailing Shariah law, along with the common law system, in Pakistan and its impact on the status of women residing in Pakistan. In the beginning, the chapter opens up with the prime focus on elaborating the concept, origin and historical background of Shariah law. As Shariah law is commonly referred to as the Islamic law or Islamic Jurisprudence, it is related to the teachings of the Holy Quran and Sunnah of the Prophet (Pbuh) and this paper seeks to address specifically those teaching of the Shariah that are related to Muslim women. The paper then chalks out in detail the historical background of Shariah law system in Pakistan, since independence to date. Moving on, the paper then focuses on analyzing the status of women in Pakistan through the lens of prevailing Shariah law system. The status of women is analyzed on two basic parameters, that is, on the basis of their rights provided under Shariah law and on the basis of their rights under constitutional and other legal statues in Pakistan. In the end, the chapter concludes with comprehensive essence of the entire topic.